Evaluation of Digital-based Al-Qur'an Tahfizh Learning in Boarding School - Masrur, Muhammad; Muhtarom, Muhtarom; Salamun, Salamun; Kusuma, Nurhadi; Wahyudi, Apri; Khotimah, Sita Husnul (TARBIYA: Journal of Education in Muslim Society, 2025)
AbstractIslamic boarding schools (pesantren) as traditional Islamic educational institutions in Indonesia face challenges in integrating digital technology into their learning processes. This study aims to analyze the implementation of digital learning evaluation in the Qur'anic tahfizh program at Insan Mulia Islamic Boarding School (IMBOS) in Pringsewu, Lampung, and assess its impact on educational quality. The research employs a descriptive qualitative approach, with data collected through in-depth interviews and participatory observation involving 52 tahfizh teachers (muhafizh/muhafizhah) overseeing 104 study groups (halaqah). Findings reveal that IMBOS has adopted two digital evaluation platforms: (1) a web-based system integrated with a mobile application for attendance monitoring, and (2) a spreadsheet application for assessing memorization progress. Data analysis indicates three key benefits of this technological implementation: enhanced evaluation efficiency through real-time monitoring, improved assessment accuracy via data visualization, and early detection of learning difficulties. These findings reinforce the critical role of digital transformation in improving the effectiveness of tahfizh education while providing a practical model for other Islamic boarding schools to adopt educational technology.AbstrakPesantren sebagai institusi pendidikan Islam tradisional di Indonesia menghadapi tantangan untuk mengintegrasikan teknologi digital dalam proses pembelajaran. Penelitian ini bertujuan menganalisis implementasi evaluasi pembelajaran digital dalam program tahfizh Al-Qur'an di Pondok Pesantren Insan Mulia (IMBOS) Pringsewu, Lampung, serta mengukur dampaknya terhadap kualitas pendidikan. Metode penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam dan observasi partisipatif terhadap 52 guru tahfizh (muhafizh/muhafizhah) yang membina 104 kelompok belajar (halaqah). Hasil penelitian mengungkapkan bahwa IMBOS mengadopsi dua platform evaluasi digital: (1) sistem web terintegrasi aplikasi mobile untuk monitoring kehadiran, dan (2) aplikasi spreadsheet untuk penilaian pencapaian hafalan. Analisis data menunjukkan bahwa implementasi teknologi ini menghasilkan tiga manfaat utama: peningkatan efisiensi proses evaluasi (real-time monitoring), akurasi penilaian yang lebih baik melalui visualisasi data, serta kemampuan deteksi dini kesulitan belajar. Temuan ini memperkuat argumentasi tentang peran kritis transformasi digital dalam meningkatkan efektivitas pendidikan tahfizh, sekaligus menawarkan model praktis bagi pesantren lain dalam mengadopsi teknologi pendidikan. How to Cite: Masrur, M., Muhtarom, Salamun, Kusuma, N., Wahyudi, A., & Khotimah, S. H. (2025). Evaluation of digital-based Al-Qur'an tahfizh learning in boarding school. TARBIYA: Journal of Education in Muslim Society, 12(1), 1-16. doi:10.15408/tjems.v12i1. 44758.